Efek perlakuan pack carburizing dan media korosif pada baja AISI 1045 terhadap laju korosi - Suarsana, I Ketut; Astika, I Made; Agus Suryawan, I Gede Putu (Jurnal Energi Dan Manufaktur; Vol 14 No 2 (2021)DO - 10.24843/JEM.2021.v14.i02.p01, 2022)
Corrosion is a destructive symptom that affects the properties of a metal, which means that the physical properties and quality of the metal decrease due to the electrochemical reaction between the metal and its environment so that the strength of the metal decreases. Corrosion control can be used to avoid the negative impact of corrosion, through the pack carburizing treatment method. The material used in this research is AISI 1045 steel. To determine the effect of pack carburizing on the corrosion rate of steel, the research was carried out by varying the suhue of the carburizing pack and corrosive media. In this study, the pack carburizing process with suhue variations used was 750°C, 850°C, 950°C and the corroding media used were air, fresh water and sea water. This was observed in accordance with the application of AISI 1045 material. The corrosive process through corrosive media was carried out for 720 hours. The results showed that pack carburized steel at a temperature of 950°C had a lower corrosion rate than pack carburized steel at 750°C. Also, air corrosive media provides a lower corrosion rate compared to seawater corrosion rate.